Resistensi Antimikroba: Pengetahuan, Sikap, dan Kewaspadaan pada Komunitas Lokal Bali: - - Dewi, Ni Luh Putu Sastrani; Widowati, I Gusti Ayu Rai; Wirajaya, Made Karma Maha; Maharianingsih, Ni Made (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2024)
Antimicrobial resistance (AMR) concerns may arise as a result of improper antibiotic use. Bacterial resistance to antibiotics, which has been identified by the WHO as one of the most serious threats to public health, can be worsened by a lack of public understanding of proper antibiotic use. The objective of this research was to find out the level of community knowledge, attitudes, and awareness about AMR. A validated questionnaire was adopted to conduct purposeful interviews with locals of Kerobokan Kaja Village during February and March 2023 to conduct the cross[1]sectional survey. There were 110 total responses (100% response rate). Most respondents (37 [33.3%]) are between the ages of 18 and 27; 56 [50.9%] are women; and 78 [70.9%] have completed secondary school.; (41 [37.3%]) work as private employees; and received minimum wages (41 [37.3%]). The findings indicated that more than half of the population (70 [63.3%]) had adequate knowledge regarding the use of antibiotics, adequate attitudes (64 [58.2%]), and fair awareness of AMR (63 [57.3%]). The results of the Spearman's Rank test reveal a moderately strong correlation between knowledge and AMR awareness (Sig.2-tailed=0.000; p-value